"WHICH Headache to Investigate, WHEN, and HOW?". Issue 10 (31st October 2016) - Ravishankar, K.
Abstract : Premise: Headache is a common problem in medical practice. The International Classification of Headache Disorders (ICHD‐3 beta) 1 divides all headaches into two broad categories. Most headaches seen in practice belong to the category of primary headaches, where there is no underlying structural cause identifiable. Less than 10% headaches in practice belong to the category of secondary headaches where there is an underlying condition, that can sometimes be ominous and life‐threatening. Problem: Fear of missing a treatable serious secondary headache disorder is the most important reason why we need to investigate headache patients. There is no dilemma in investigating the patient when the clinical presentation is straightforward but when the headache presents differently or with 'red flags, ' it can sometimes be quite challenging to order the right investigation and rapidly arrive at the right diagnosis. Potential solutions: This article looks at some of the elusive headache scenarios and outlines an approach that addresses the issue of 'appropriate' investigation in the headache patient. With advancing technology and increasing expertise, the author feels it is time now to do away with the practice of ordering an exhaustive battery of tests in all headache patients. With experience, clinicians can learn to choose tests judiciously and order specific tests based on a working diagnosis. As the title suggests, knowing 'WHEN to order WHAT test in WHICH headache patient? ' forms the theme of this article.